Guinea : Joint Staff Assessment of the Poverty Reduction Strategy Paper. (IMF Staff Country Reports; Country Report ;, 2004)
The paper analyzes the Joint Staff Assessment of the Poverty Reduction Strategy Paper (PRSP) Progress Report for Guinea. The report assesses progress made in implementing the PRSP during the calendar years 2002 and 2003, and lays out the measures the government is pursuing to achieve its policy objectives. The IMF staff agrees with the progress report conclusion that efforts have been made over the last two years to advance the poverty reduction strategy, even as the economic environment became more difficult and Guinea's program with the IMF went off-track.